Designing a Firing Control System on S-60 57mm Cannon - As'ad, Kurnia Gunadi; Setiawan, Rachmad; Rameli, Moch (Faculty of Engineering, Universitas Tanjungpura, 2021)
The firing system on the S-60 57mm cannon uses the foot of the cannon crew, which is very dangerous with the position of the crew on top of the cannon when firing. So, a firing system that can be remotely controlled by a computer is required. The design of the S-60 57mm gun firing control system uses a personal computer (PC) as the firing command input, with data communication using WiFi received by the Atmega8535 microcontroller as a voltage regulator for solenoids. The solenoid has a tensile force to drive the hydraulic system where the actuator functions to drive the firing cylinder. Accelero sensor MMA7361, as a variable controller in firing, provides input data simulating the tilt position of the cannon, the position of the 0g sensor is simulated by the cannon in a balanced position. From the test results, there is a difference in sensor designation data with arc angles i.e., angle X by 2.83 degrees and angle Y by 1.86 degrees. The magnetic field produced by the solenoid 0.53 T can attract a maximum load of 20 kg. By changing the distance ratio of mechanical lever to 39.11 cm and 8.89 cm, the solenoid can drive an 88-kg firing cylinder.